2013
DOI: 10.1002/nbm.3050
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of MRSI brain temperature mapping at 1.5 and 3 T

Abstract: MRSI permits the non-invasive mapping of brain temperature in vivo, but information regarding its reliability is lacking. We obtained MRSI data from 31 healthy male volunteers [age range, 22–40 years; mean ± standard deviation (SD), 30.5 ± 5.0 years]. Eleven subjects (age range, 23–40 years; mean ± SD, 30.5 ± 5.2 years) were invited to receive four point-resolved spectroscopy MRSI scans on each of 3 days in both 1.5-T (TR/TE = 1000/144 ms) and 3-T (TR/TE = 1700/144 ms) clinical scanners; a further 20 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 35 publications
5
45
2
Order By: Relevance
“…It is not clear whether these temperature variations are due to physiological (e.g., molecular environment) differences among these brain regions, or other effects related to magnetic susceptibility‐induced frequency shifts (a limitation of 1 H‐MRS for temperature mapping) 10 . However, larger within‐subject variability (0.28°C) was observed for repeated temperature measurements in similar brain regions (i.e., parietal, precuneus) in the present study, compared with Thrippleton et al (0.14°C) 41 . Differences in the brain temperature reproducibility between the two studies could be attributed to differences in study design, acquisition factors and brain parcellation methods.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…It is not clear whether these temperature variations are due to physiological (e.g., molecular environment) differences among these brain regions, or other effects related to magnetic susceptibility‐induced frequency shifts (a limitation of 1 H‐MRS for temperature mapping) 10 . However, larger within‐subject variability (0.28°C) was observed for repeated temperature measurements in similar brain regions (i.e., parietal, precuneus) in the present study, compared with Thrippleton et al (0.14°C) 41 . Differences in the brain temperature reproducibility between the two studies could be attributed to differences in study design, acquisition factors and brain parcellation methods.…”
Section: Discussioncontrasting
confidence: 71%
“…Differences in the brain temperature reproducibility between the two studies could be attributed to differences in study design, acquisition factors and brain parcellation methods. For example, in Thrippleton et al, 41 four consecutive scans within the same day were acquired to test the reproducibility of brain temperature measurements within a 10 mm brain slice, while in the present study three repeated scans were acquired with a mean interval of 1 week between the scan sessions. Larger variability for repeated measurements might be expected due to instrument variability, subject alignment and/or biological variability.…”
Section: Discussionmentioning
confidence: 86%
“…The temperature calibration curves for the ionic solutions showed small differences between this study at 3 T and that of Vescovo et al at 1.5 T, although this does not rule out significant effects at higher field strengths or in more complex microenvironments. An MRSI based MR thermometry study investigating field strength effects, 1.5 T versus 3 T, also showed that no magnetic field effects were observed on the temperature calibration curve using an ionic concentration solution of 56 mM . In contrast, the calibration curves with varying protein concentration presented here did show different mean results compared with those of Vescovo et al at 1.5 T (see Fig.…”
Section: Discussioncontrasting
confidence: 44%
“…Small frequency drifts, slow organ motion components, or magnetic field inhomogeneities are no longer a source of uncertainties in the MR thermometry because the peak difference is measured in the same voxel at the same time. Feasibility studies of using SVS for temperature information in animal 27,28,30 or in human brain 31,32 are reported. The difference in fat and water peak yields information about the temperature inside the investigated voxel: measured power spectrum (green) and fitted power spectrum (blue).…”
Section: Introductionmentioning
confidence: 99%